(untitled) (Research, Society and Development, 2023)
Aiming to promote improvements in mental capacity such as attention, concentration and memory, healthy individuals have resorted to the use of medications that supposedly enhance cognitive performance, generating Pharmacological Cognitive Enhancement. The present study aimed to carry out a literature review investigating what supporters of this phenomenon report about its benefits and adverse events, seeking to promote reflections on the topic. This is a systematic, basic, transversal, exploratory and qualitative literature review research, whose guiding question was prepared in accordance with the PICO strategy, as well as the recommendations of the PRISMA checklist. To obtain the data, a survey of publications in the VHL was carried out, using the descriptors ’pharmacological cognitive enhancement’, ’psychopharmaceuticals and students’, ’nootropics and students’, ’intelligence drugs and students’, ’psychostimulants and students’, ’ lisdexamfetamina and students’, ’methylphenidate and students’, ’donepezil and students’, ’modafinil and students’ and ’piracetam and students’. The inclusion criteria were: published between 2017 and 2023; available in Spanish, English or Portuguese and of a quantitative nature. After reading the titles and abstracts, 9 scientific articles were selected for full reading, followed by analysis. The findings were grouped into two thematic approaches, benefits and adverse events. It was found that there are numerous self-declared benefits: a feeling of cognitive enhancement (improvement in academic performance such as concentration, attention, reasoning and memory) and a feeling of well-being, as well as a reduction in fatigue, stress and sleep. Regarding adverse events, the results indicate that most of the effects cited in the literature were reported by research participants who use or have used the neurostimulant. It is concluded that new studies need to be carried out to investigate the cost-benefit of this practice, clarifying the real effectiveness of the advantages in terms of adverse events, especially in the long term.